The Service Quality, Patient Satisfaction And It’s Impact To Patient Loyalty at X Hospital - Satyawati; Margaretha Pink Berlianto (Institute of Computer Science (IOCS), 2022)
This research aims to analyze the positive effect 5Q dimension of service quality; quality of object, quality of process, quality of infrastructure, quality of interaction, quality of atmosphere on patient satisfaction, the positive effect of patient satisfaction on patient loyalty and the positive effect of trust and commitment on patient loyalty. This study used quantitative research and data collection was collected using questionnaire. The target population of this research were people that have admitted as in patiens at X hospital Bogor and willing to be respondents of this research. The number of samples were determined to be which 219 samples.The sampling technique use was purposive sampling. Partial Least Square-Structural Equation modelling (PLS-SEM) is applied to this study. The result of data analysis showed that quality of object, quality of infrastructure, quality of interaction, dan quality of atmosphere have positive effect on patient satisfaction, Patient satisfaction and trust have positive effect on patient loyalty. Quality of process has a negative effect on patient satisfaction. Lastly, commitment has a negative effect on patient loyalty.